2021
DOI: 10.3390/ani11082283
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Fecal Microbiota Associated with a Broad-Spectrum Antimicrobial Administration in Hospitalized Neonatal Foals with Probiotics Supplementation

Abstract: There is a wide array of evidence across species that exposure to antibiotics is associated with dysbiosis, and due to their widespread use, this also raises concerns also in medicine. The study aimed to determine the changes on the fecal microbiota in hospitalized neonatal foals administered with broad-spectrum antimicrobials and supplemented probiotics. Fecal samples were collected at hospital admission (Ta), at the end of the antimicrobial treatment (Te) and at discharge (Td). Feces were analysed by next-ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 77 publications
0
6
1
Order By: Relevance
“…TMS administration was associated with significant decreases in richness but not diversity, indicating that this antibiotic mainly affects the less abundant bacteria. Several studies have investigated the impact of antimicrobials on the equine fecal microbiota [8,9,11,[27][28][29], but such discussion is beyond the scope of this report.…”
Section: Discussionmentioning
confidence: 99%
“…TMS administration was associated with significant decreases in richness but not diversity, indicating that this antibiotic mainly affects the less abundant bacteria. Several studies have investigated the impact of antimicrobials on the equine fecal microbiota [8,9,11,[27][28][29], but such discussion is beyond the scope of this report.…”
Section: Discussionmentioning
confidence: 99%
“…Our study did not observe a significant effect of diet (roughage and/or concentrates) on microbiota composition. This contrasts with previous studies in which dietary effects on the intestinal microbiota have been demonstrated [51][52][53] . However, in these studies, larger contrasts in diet between studied groups were tested (e.g., no concentrate feeding vs. high level of concentrate feeding).…”
Section: Dietcontrasting
confidence: 99%
“…We demonstrated an effect of farm/location on microbiota composition in our study. A previously published study showed relatively low variation in microbiota composition between horses housed in the same environment, indicating interaction patterns across horses housed in the same environment 51 . The effects of location on microbiota composition have been reported previously in domesticated and (semi-) feral horses 19,34,39,56,57 .…”
Section: Locationmentioning
confidence: 89%
See 1 more Smart Citation
“…The most important factors in proper foal management and prevention of diarrhea are sufficient and timely intake of high-quality colostrum and maintenance of hygienic environmental conditions [ 3 , 4 ], but prophylactic and therapeutic pharmaceutical management also play a significant role [ 48 , 49 ].…”
Section: The Appeal Of Microbiota Manipulationmentioning
confidence: 99%